Electricity Consumption, Roads and Their Infrastructure; Strategies to Increase Per Capita Income and Reduce Poverty in East Nusa Tenggara - Dian Anggraeny Rahim; Atik Isniawati (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2025)
Low electricity consumption, restricted road length, and insufficient road infrastructure are believed to contribute to low per capita income and high poverty rates in East Nusa Tenggara. To substantiate this hypothesis, a study was undertaken in that province and the population are 21 districts and one city. This study analyzed data from 2019 to 2023 and utilized the Panel Data Regression analysis method. The findings of this study indicate that electricity consumption significantly impacts the increase in per capita income. Conversely, to alleviate poverty, the variable of road length exerts a significant influence. However, road infrastructure variables have shown no effect on boosting per capita income or reducing poverty. Formulation of strategies to diminish poverty while augmenting per capita income was conducted through the Analytical Network Process (ANP) analysis tool, involving nine stakeholders and decision-makers within the region.  ANP is a supportive tool in decision-making processes  that has many criterias and sub criterias. The agreed-upon strategy focuses on three primary priorities: enhancing community electricity consumption, extending road lengths, and enhancing road infrastructure.